Calcio e pedagogia - Daniela Sarsini (Studi sulla Formazione)
The article aims to briefly highlight the cognitive, emotional, ethical and social implications of the game of soccer. Beginning with the classical concept of "arete," it reflects on the relationship between the sport and pedagogy.